2017
DOI: 10.18632/oncotarget.15211
|View full text |Cite
|
Sign up to set email alerts
|

ATM mutations and E-cadherin expression define sensitivity to EGFR-targeted therapy in colorectal cancer

Abstract: EGFR-targeted therapy is a key treatment approach in patients with RAS wildtype metastatic colorectal cancers (CRC). Still, also RAS wildtype CRC may be resistant to EGFR-targeted therapy, with few predictive markers available for improved stratification of patients. Here, we investigated response of 7 CRC cell lines (Caco-2, DLD1, HCT116, HT29, LS174T, RKO, SW480) to Cetuximab and correlated this to NGS-based mutation profiles, EGFR promoter methylation and EGFR expression status as well as to E-cadherin expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Because patients with RAS wild‐type CRC can be non‐responders to EGFR‐targeted therapy, Geibler et al analyzed cell lines and tumor specimens to identify prediction markers by NGS, EGFR methylation and expression, and E‐cadherin expression. The authors revealed ATM mutations and low E‐cadherin expression as novel supportive predictive markers . Adua et al analyzed primary tumor and liver metastasis samples from 7 KRAS wild‐type patients and compared the genotypes of 22 genes associated with anti‐EGFR before and after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because patients with RAS wild‐type CRC can be non‐responders to EGFR‐targeted therapy, Geibler et al analyzed cell lines and tumor specimens to identify prediction markers by NGS, EGFR methylation and expression, and E‐cadherin expression. The authors revealed ATM mutations and low E‐cadherin expression as novel supportive predictive markers . Adua et al analyzed primary tumor and liver metastasis samples from 7 KRAS wild‐type patients and compared the genotypes of 22 genes associated with anti‐EGFR before and after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The authors revealed ATM mutations and low E-cadherin expression as novel supportive predictive markers. 8 Adua et al analyzed primary tumor and liver metastasis samples from 7 KRAS wild-type patients and compared the genotypes of 22 genes associated with anti-EGFR before and after chemotherapy. The results showed marked genotypic differences between pre-and post-treatment samples, which were likely attributable to tumor cell clones selected by therapy.…”
mentioning
confidence: 99%
“…This mutation, in addition to the pathogenic variant (C>T, rs121913530, Gly12Ser) were detected in patient ID 8. Both variants were shown to discriminate conventional adenoma from CRC [25]. The remaining pathogenic KRAS variants were found in exon 3 (G>A, rs104894364, Thr58Ile patient ID 20) and in exon 4 (C>T, rs121913527, Ala146Thr patient ID 10), both are well-known pathogenic variants in CRC [26].…”
Section: Kras Pathogenic and Likely Pathogenic Variantsmentioning
confidence: 99%
“…Finally, PIK3CA, which plays important role in MAPK pathway, has got pathogenic missense variants in patient ID 4 (G>A, rs104886003, Glu545Lys) and patient ID 16 (A>G, rs121913279, His1047Arg,). Both variants are PIK3CA hotspot somatic mutations [57] with good response to cetuximab [25]. Interestingly, patient ID 4 is a very good example of a possible interplay between pathways of TP53, KRAS and PI3K.…”
Section: Tp53 Showed the Highest Percentage Of Germline Inherited Mutmentioning
confidence: 99%
“…The authors described three hypermutated tumors with MSI-H or POLE mutation and ERBB2 amplified tumors (5% of cases) as well, which might benefit of anti-PD-1 or HER2-targeted therapy in absence of RAS/RAF mutations, respectively. Again, a recent study on both cell lines and tumor specimens [ 83 ] highlighted the importance of NGS in detecting genes potentially involved in the resistance to anti-EGFR therapy in KRAS wild-type patients. The authors analyzed the response of 7 CRC cell lines to cetuximab as well as primary tumors, liver and lung metastasis from 25 CRC patients treated with cetuximab or panitumumab, by evaluating NGS (Illumina) mutation profiles of 48 cancer-related genes, EGFR and E-cadherin expression.…”
Section: Ngs In Crcmentioning
confidence: 99%